2016
DOI: 10.3329/bjpt.v23i2.30851
|View full text |Cite
|
Sign up to set email alerts
|

Numerical taxonomic analysis in leaf architectural traits of some <i>Hoya</i> R. Br. species (Apocynaceae) from Philippines

Abstract: The present study examines the leaf variations in leaf traits of four Hoya R. Br. species from Philippines namely: (1) H. buotii Kloppenburg, (2) H. halconensis Kloppenburg, (3) H. mindorensis Schlechter red bearing flowers; and (4) H. mindorensis Schlechter yellow bearing flowers. Leaf samples (n= 30 leaves) were collected from each plant group and measured with nine architectural traits. The results showed variability in the leaves using univariate and multivariate analysis. Data ordination depicted variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…One of the key reproductive characters to evaluate when describing Hoyas is the presence of five staminal coronal lobes attached to the staminal column [12]. In the absence of reproductive organs, the use of leaf characters can be used to described Hoyas, such as the study conducted by Jumawan & Buot [13] on the Hoya diversity in the Philippines.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key reproductive characters to evaluate when describing Hoyas is the presence of five staminal coronal lobes attached to the staminal column [12]. In the absence of reproductive organs, the use of leaf characters can be used to described Hoyas, such as the study conducted by Jumawan & Buot [13] on the Hoya diversity in the Philippines.…”
Section: Introductionmentioning
confidence: 99%
“…ex L. (Antonio and Buot 2021), and Hoya R. Br. (Salvaña and Buot 2014;Villareal and Buot 2015;Jumawan and Buot 2016;Torrefiel and Buot, 2017;Tan and Buot 2018;Baltazar and Buot, 2019;Paguntalan and Buot 2019). These researches revealed that leaf architecture has enormous potential as a tool for solving taxonomic problems.…”
Section: Introductionmentioning
confidence: 99%
“…No genus revision has been published as of this writing; the need for this revision persists amid the recent increase in the popularity of urban gardening, which gives even more public significance to identifying plants properly. In the interim, several studies have utilized leaf architecture analysis to offer supplemental information on the delineation of some controversial Hoya species, such as H. incrassata vs. H. crassicaulis (Villareal and Buot 2015), H. buotii vs. H. halconensis (Jumawan and Buot 2016), among H. carandangiana, H. bicolensis, and H. camphorifolia (Torrefiel and Buot 2017), H. merrillii vs. H. quinquenervia (Paguntalan and Buot 2019), to name a few.…”
Section: Introductionmentioning
confidence: 99%